Web Information Systems and Mining International Conference, WISM 2010, Sanya, China, October 23-24, 2010. Proceedings - Wang, Fu Lee.; Gong, Zhiguo; Luo, Xiangfeng; Lei, Jingsheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the International Conference on Web Information Systems and Mining, WISM 2010, held in Sanya, China, on October 23-24, 2010. The 54 revised full papers presented in this volume were carefully reviewed and selected from 603 submissions. The papers are organized in topical sections on applications of web information systems, applications of web mining, distributed systems, e-government and e-commerce, geographic information systems, information security, intelligent networked systems, management information systems, mobile computing, web content mining, web information classification, web information retrieval, web services and e-learning, and XML and semi-structured data.
Applications of Web Information Systems -- An Improving Multi-Objective Particle Swarm Optimization -- Study on RSA Based Identity Authentication Algorithm and Application in Wireless Controlling System of Aids to Navigation -- Invariant Subspaces for Some Compact Perturbations of Normal Operators -- Research of Cooperative Geosteering Drilling Virtual System Based on Network -- Optimization of Storage Location Assignment for Fixed Rack Systems -- Evaluation Query Answer over Inconsistent Database with Annotations -- Research and Implementation of Index Weight Calculation Model for Power Grid Investment Returns -- Applications of Web Mining -- An Improved Algorithm for Session Identification on Web Log -- A Chinese Web Page Automatic Classification System -- Towards a Quality-Oriented Real-Time Web Crawler -- Research on the Value of Business Information Online Based on Fuzzy Comprehensive Evaluation -- A Clustering Algorithm Based on Matrix over High Dimensional Data Stream -- Distributed Systems -- A Dynamic Dispatcher-Based Scheduling Algorithm on Load Balancing for Web Server Cluster -- Nature of Chinese Thesaurus Automatic Construction and Its Study of Major Technologies in Digital Libraries -- Research on the Resource Monitoring Model Under Cloud Computing Environment -- E-Government and E-Commerce -- A New Photo-Based Approach for Fast Human Body Shape Modeling -- A Multi-Criteria Analysis Approach for the Evaluation and Selection of Electronic Market in Electronic Business in Small and Medium Sized Enterprises -- Geographic Information Systems -- A WebGIS and GRA Based Transportation Risk Management System for Oversea Oil Exploitation -- Prediction of Pine Wilt Disease in Jiangsu Province Based on Web Dataset and GIS -- An Approach for Integrating Geospatial Processing Services into Three-Dimensional GIS -- Parallel K-Means Clustering of Remote Sensing Images Based on MapReduce -- Information Security -- Enhancing Distributed Web Security Based on Kerberos Authentication Service -- A New Scheme for Protecting Master-Key of Data Centre Web Server in Online Banking -- An Automated Worm Containment Scheme -- RBAC-Based Access Control Integration Framework for Legacy System -- A Pseudo Random Numbers Generator Based on Chaotic Iterations: Application to Watermarking -- A Secure Protocol for Point-Segment Position Problem -- Learning Automata Representation of Network Protocol by Grammar Induction -- Gene-Certificate Based Model for User Authentication and Access Control -- A New Data Integrity Verification Mechanism for SaaS -- An Exquisite Authentication Scheme with Key Agreement Preserving User Anonymity -- Towards a Dynamic Federation Framework Based on SAML and Automated Trust Negotiation -- Intelligent Networked Systems -- Research and Application of FlexRay High-Speed Bus on Transformer Substation Automation System -- A Task Scheduling Algorithm Based on Load Balancing in Cloud Computing -- The Accuracy Enhancements of Virtual Antenna for Location Based Services -- Management Information Systems -- Research on the Production Scheduling Management System Based on SOA -- A Requirement-Driven Approach to Enterprise Application Development -- Mobile Computing -- ESA: An Efficient and Stable Approach to Querying Reverse k-Nearest-Neighbor of Moving Objects -- The Research of Efficient Dual-Port SRAM Data Exchange without Waiting with FIFO-Based Cache -- Web Content Mining -- Extracting Service Aspects from Web Reviews -- Clustering the Tagged Resources Using STAC -- Advertising Keywords Extraction from Web Pages -- Automatic Topic Detection with an Incremental Clustering Algorithm -- Web Information Classification -- Three New Feature Weighting Methods for Text Categorization -- Algorithms of BBS Opinion Leader Mining Based on Sentiment Analysis -- Entity Relationship Extraction Based on Potential Relationship Pattern -- Web Information Retrieval -- On Arnoldi Method Accelerating PageRank Computations -- A Framework for Automatic Query Expansion -- Web Services and E-Learning -- WSCache: A Cache Based Content-Aware Approach of Web Service Discovery -- A Novel Local Optimization Method for QoS-Aware Web Service Composition -- Preference-Aware QoS Evaluation for Cloud Web Service Composition Based on Artificial Neural Networks -- Software Architecture Driven Configurability of Multi-tenant SaaS Application -- XML and Semi-structured Data -- Parallel Accessing Massive NetCDF Data Based on MapReduce -- On Well-Formedness Rules for UML Use Case Diagram.
Keywords: Computer science; Software engineering; Database management; Data mining; Information storage and retrieval systems; Information systems; Multimedia systems; Computer Science; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Software Engineering; Data Mining and Knowledge Discovery; Multimedia Information Systems